(untitled) (Journal of the Association for the Study of Australian Literature, 2013)
Taking a cue from T.S. Eliot’s ’The Wasteland’ this article considers the different attitudes to the Australian city, particularly Sydney, in the poetry of the 1920s. It argues that in the 1920s there was a shift from the gloomy view of the city of the late nineteenth century–evident in the work of Henry Lawson and Christopher Brennan–to an embrace of the modern aspects of Sydney, and expressed in light verse by Kenneth Slessor, Colin Wills and Ronald McCuaig.